KEMAMPUAN BUBUK EKSTRAK DAUN CINCAU HIJAU (Premna oblongifolia Merr.) DALAM MENSTIMULASI PERTUMBUHAN Lactobacillus casei subsp. rhamnosus - Nurmalasari, Dwi Putri; Semadi Antara, Nyoman; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 4 (2017): Desember, 2017)
Dietary fiber with excellent fermentability can be categorized as prebiotics, one of which was green grass jelly. The objective of this research was to know the concentration of green grass leaf extract powder to stimulate the growth of  Lactic Acid Bacteria ( Lactobacillus casei subsp. rhamnosus ). In vitro experiments were performed in laboratory with a concentration treatment of green grass leaf powder and glucose as a control. The medium used was yeast-peptone medium added with 1% glucose, 0% green grass leaf extract powder, 0.1% green grass leaf extract powder, 0.2% green grass leaf extract powder, 0.3% green grass leaf extract powder, 0.4% green grass leaf extract powder, and 0.5% green grass leaf extract powder. Fermentation was carried out at 37 o C with a fermentation time of 9 hours. The experimental results showed that the concentration of green grass leaf powder extract of 0.2% was the best, in performance to stimulating growth of LAB. This concentration of the extract was the critical concentration, since the process of medium solidification was occured at the extract concentration of more than 0.2%. Keywords : Lactobacillus casei subsp. rhamnosus , green grass jelly, prebiotic.